Effects of Using Eggshell Waste as a Calcium Source in the Diet of Rhode Island Red Roosters on Semen Quality, Gonadal Development, Plasma Calcium and Bone Status - Nirat Gongruttananun (Agriculture and Natural Resources, 2011)
A 10 wk trial was conducted to investigate the effect of using ground, sterilized eggshell as a calcium source in breeder male diets. Live performance, semen quality, gonadal and visceral organ characteristics, plasma calcium concentration and bone mineralization were evaluated. Forty-five Rhode Island Red cockerels aged 25 wk were caged individually in a conventional open-sided house. The birds were randomly divided into three groups, each group consisting of 15 birds. Group 1 (Control) was provided with a standard breeder ration which contained all the calcium carbonate as fine limestone, whereas Groups 2 and 3 were placed on diets in which 50% and 100%, respectively, of the limestone was replaced with ground eggshell. The birds were given free access to food and water, and exposed to a 16L:8D photoperiod. Throughout the study, body weight, feed consumption, spermatocrit, semen volume, sperm concentration and total sperm number/ejaculation of the three bird groups were not significantly (P > 0.05) different. Seminal plasma pH and Ca++ concentration were not affected by dietary treatments. Autopsies at the end of the study showed that comb weight, testes weight, ductus deferens weight and length, and giblets weight of the birds did not differ among the treatment groups. In addition, packed cell volume and plasma calcium and phosphorus concentrations did not exhibit a difference among cockerels fed the different calcium sources. No significant differences were found in any aspect of the tibia parameters (weight, length, breaking strength and ash content). The weights and lengths of the humerus from the three bird groups were comparable whatever the calcium source. Similar observations were also found in the parameters of the tarsometatarsus and keel bones. It was apparent that eggshell can be fully used as a calcium source in diets without any detrimental effects on the live performance, semen quality, reproductive development and calcium homeostasis of breeder male chickens.